Reflections on the first year of integrity hour: An online community of practice for academic integrity - Eaton, Sarah Elaine; Moya Figueroa, Beatriz; Butterworth, Carina; Feledichuk, Donna; Leslie, Kathleen; Lothian, Jane; Murray, Joel; Soodeen, Claudius; Wheatley, Bronwen (Canadian Perspectives on Academic Integrity, 2021)
Integrity Hour first convened in March 2020, in response to the rapid pivot to emergency remote teaching during COVID-19. After a year, this online community of practice (CoP) is still going strong. We collectively reflect on how the first year of Integrity Hour has informed our understanding of how to uphold and enact academic integrity and impacted how we work with students, support our colleagues, and make decisions.